Estudo do controle de vibração de uma viga engastada por meio de absorvedores dinâmicos de vibração - Stresser, Janicely Fatima (2021)
Beam-type structural elements are commonly used in civil construction, as well as in other areas of engineering. During their useful life, these structures are subject to different forms of loading, both static and dynamic, which, under specific conditions, can assume a state of vibration that can compromise the entire structural system. The objective of this work was to study the optimal parameters of a Dynamic Vibration Absorber (DVA) for the vibration control of a cantilever beam type structure. For this, a dynamic analysis of the primary structure, using the Finite Element Method (FEM), was performed to identify the vibration modes and identify the frequency response function. From the dynamic characteristics of the primary structure, the ideal parameters of the DVA were determined: stiffness, mass ratio and optimal damping, for the control of the beam's first natural frequency. The DVAs were modeled as a cantilever beam with a concentrated mass at the tip. These were sized in two different ways, the first considering a frequency ratio equal to one and damping entered after determining the mass and stiffness parameters, and the second for a frequency ratio other than one and the optimum damping added before determining the mass and stiffness parameters. After dimensioning, the DVAs were coupled to the primary structure and the dynamic analyzes were performed again for each dimensioned DVA, where a reduction in vibration amplitude was observed. For the first case it was observed that the DVAs considerably reduced the amplitudes, however it operated as a system not optimally tuned. In the second case, the DVAs showed good performance in reducing amplitudes, however, the responses were not satisfactory for a device with optimal sizing parameters. This fact is due to the difference between the theoretically and numerically calculated natural frequencies. To assess the difference in the responses of the second case, the third case was performed through a theoretical analysis considering the system in free vibration, in which the results proved to be appropriate for an optimally tuned device. For all sized DVAs coupled to the primary structure, the results were satisfactory, in order to show their efficiency in relation to the control of the first vibration mode of the beam studied in this work.